2019
DOI: 10.3389/fenrg.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Various Pyrolysis Liquids From Biosolids on Methane Production Yield

Abstract: Aqueous pyrolysis liquid (APL) is a high-COD byproduct of wastewater biosolids pyrolysis that is comprised of numerous complex organic compounds and ammonia nitrogen (NH 3 -N). One potential beneficial use of APL is as a co-digestate to produce more biogas in anaerobic digesters. However, some APL organics and NH 3 -N are known to inhibit methane-producing microbes. Autocatalytic pyrolysis which uses previously-produced biochar as a catalyst during biosolids pyrolysis, increases energy-rich py-gas while elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In an effort to remove NH 3 -N that could inhibit methanogenesis, some catalyzed and non-catalyzed APL samples (30 mL) were aerated for 9 h at 2 L/min air flow (1 atm, 20 • C) to strip NH 3 -N [7]. Volatile constituents such as ethylbenzene and styrene were also removed during air stripping (Table S1) [13].…”
Section: Apl Production and Apl Nh 3 -N Air Strippingmentioning
confidence: 99%
See 4 more Smart Citations
“…In an effort to remove NH 3 -N that could inhibit methanogenesis, some catalyzed and non-catalyzed APL samples (30 mL) were aerated for 9 h at 2 L/min air flow (1 atm, 20 • C) to strip NH 3 -N [7]. Volatile constituents such as ethylbenzene and styrene were also removed during air stripping (Table S1) [13].…”
Section: Apl Production and Apl Nh 3 -N Air Strippingmentioning
confidence: 99%
“…However, previous studies have shown anaerobic digestion is challenging since APL contains organic compounds that are known to inhibit methanogens and reduce or stop digester methane production [10,11,15]. In addition, high ammonia nitrogen (NH 3 -N) concentration in APL may also cause digester inhibition [13,16]. Both catalyzed and non-catalyzed APLs used in this study contained high NH 3 -N concentrations.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations